Physical Education Teacher Strategies to Improving Student Learning Outcomes Through Publication of Work Results - Williyanto, Septian; Masri, Masri; Santoso, Nurhadi; Wiyanto, Agus (Universitas Negeri Semarang (Unnes), 2020)
Currently, physical education learning is experiencing a dilemma caused by the COVID-19 pandemic, so teachers must be able to improvise and be creative in creating distance learning models so that learning can be adequately conveyed to students. The purpose of this study was to examine the creativity and strategies of physical education teachers in improving the quality of student learning outcomes to maintain the continuity of online learning during the COVID-19 pandemic. Researchers used a descriptive qualitative approach with research subjects, namely Physical Education teachers and students of Wonosobo Public Senior High School 1. The data collection techniques used were in-depth interviews and documentation. The results showed that the form of physical education teacher strategies in improving the quality of online learning during the COVID-19 outbreak was by using the method of publishing the work of students. This method is proven effective and can increase students’ interest, motivation to learn, stimulate student discipline, and can make it easier for teachers to make assessments. The obstacle in this research is that not all students get the same facilities from their parents, both in terms of learning facilities and infrastructure at home